2008
DOI: 10.2148/benv.34.1.88
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Bus Route Crime Risk in Urban Areas: The Changing Environs of a Bus Journey

Abstract: This study attempts to examine the risk of bus route crime and how it is influenced by environmental characteristics along the bus corridor. These include changing levels of crime risk, socio-economic influences, and changes to the physical infrastructure including land use. Three urban case study areas in the UK are used. The findings suggest that the risk of bus crime along a journey is influenced by overall levels of crime (for specific categories of crime only), that the level of risk increases in high cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…Examples include the following: criminal damage at a stop or station at an unknown time, graffiti or the slashing of a seat on a vehicle at both an unknown time and location as it may only be reported when a bus or train returns to the depot at the end of the day, and pocket picking that occurs as part of a passengers journey, somewhere between departure and arrival. In addition it is very difficult to pinpoint the location of a crime that occurs on a moving vehicle, although there are studies that attempt to analyze dynamic crime events (Newton, 2005), for example the development of "hot routes" or "hot lines" (Newton, 2008;Thompson et al, 2009). …”
Section: The Limited Evidence Basementioning
confidence: 99%
See 2 more Smart Citations
“…Examples include the following: criminal damage at a stop or station at an unknown time, graffiti or the slashing of a seat on a vehicle at both an unknown time and location as it may only be reported when a bus or train returns to the depot at the end of the day, and pocket picking that occurs as part of a passengers journey, somewhere between departure and arrival. In addition it is very difficult to pinpoint the location of a crime that occurs on a moving vehicle, although there are studies that attempt to analyze dynamic crime events (Newton, 2005), for example the development of "hot routes" or "hot lines" (Newton, 2008;Thompson et al, 2009). …”
Section: The Limited Evidence Basementioning
confidence: 99%
“…There is empirical evidence that crime is concentrated at a small proportion of transport stations, stops, and hubs (Smith and Clarke 2000;Loukaitou-Sideris et al, 2002;Newton, 2004;Smith and Cornish, 2006;and Newton and Bowers, 2007) and "en route" at particular sections of public transport journeys (Newton, 2008;Tompson et al, 2009). These concentrations vary by both crime type and time of day, as will be discussed in more detail below.…”
Section: Places Times and Place Managers?mentioning
confidence: 99%
See 1 more Smart Citation
“…They conducted extensive research at three locations to identify the factors that appeared to drive crime at each, which included drug trade at one, crowding at another, and proximity to a high school in the third case. Newton (2008) focused on three bus routes in England, noting that crime was higher at bus stops in high crime areas. Similarly, LoukaitouSideris & examined factors influencing crime at 10 bus stop crime "hot spots" in Los Angeles (see also Loukaitou-Sideris, 1999).…”
Section: Bus Stop-crime Researchmentioning
confidence: 99%
“…To date, only three larger N studies (Kooi, 2007;Weisburd et al, 2012;Yu, 2009) have been undertaken and all of these find that bus stops are associated with higher crime. Prior large N studies have generally examined only direct bus stop-crime relationships, yet, many of the small N studies suggest that crime is higher at some bus stops than others, often based on characteristics of the areas surrounding bus stops (Levine et al, 1986;LoukaitouSideris, 1999;Newton, 2008). Other studies have found that rapid transit and crime are associated only under certain conditions.…”
Section: Bus Stop-crime Researchmentioning
confidence: 99%